2008
DOI: 10.1097/fpc.0b013e3283037fe4
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism discovery and functional assessment of variation in the UDP-glucuronosyltransferase 2B7 gene

Abstract: Objective UGT2B7 plays a central role in the liver-mediated biotransformation of endogenous and exogenous compounds. The genetic basis of interindividual variability in UGT2B7 function is unknown. This study aimed to discover novel gene variants of functional significance. Methods Caucasian human livers (n=54) were used. UGT2B7 was resequenced in 12 samples (6 highest and 6 lowest for the formation of morphine-3-glucuronide, M3G). Haplotype-tagging single nucleotide polymorphisms (tSNPs) were genotyped in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 23 publications
5
75
2
Order By: Relevance
“…Regarding the most common UGT2B7 nonsynonymous single nucleotide polymorphism (UGT2B7*2), it was reported that UGT2B7*2 was not associated with altered morphine 3 and 6‐glucuronidation in adult liver microsomes ( n  = 53) 33. A comprehensive PG study found that diplotypes containing haplotype #4 in UGT2B7 resulted in a significant increase in the formation of morphine 3 and 6‐glucuronidation (45% and 56%, respectively) compared with diplotypes without the haplotype #4 34. Based on the observed activity changes as a result of UGT2B7 genetic variants, the maximum velocity of UGT2B7‐mediated morphine glucuronidation in human liver microsomes was scaled from 50–150% of the default value (set at 100%), as shown in Table 1, 4, 5, 6, 14, 15, 16, 17, 18 for the simulations in virtual pediatric and adult healthy subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the most common UGT2B7 nonsynonymous single nucleotide polymorphism (UGT2B7*2), it was reported that UGT2B7*2 was not associated with altered morphine 3 and 6‐glucuronidation in adult liver microsomes ( n  = 53) 33. A comprehensive PG study found that diplotypes containing haplotype #4 in UGT2B7 resulted in a significant increase in the formation of morphine 3 and 6‐glucuronidation (45% and 56%, respectively) compared with diplotypes without the haplotype #4 34. Based on the observed activity changes as a result of UGT2B7 genetic variants, the maximum velocity of UGT2B7‐mediated morphine glucuronidation in human liver microsomes was scaled from 50–150% of the default value (set at 100%), as shown in Table 1, 4, 5, 6, 14, 15, 16, 17, 18 for the simulations in virtual pediatric and adult healthy subjects.…”
Section: Methodsmentioning
confidence: 99%
“…A study that used human livers from white individuals (n ϭ 54) identified a particular haplotype associated with UGT2B7 activity (27 ). This haplotype, with an MAF of 12%, included the intronic variant IVS1 ϩ 985AϾG (rs62298861), which was consistently correlated with increased mRNA expression and increased glucuronidation.…”
Section: Ugt2b7mentioning
confidence: 99%
“…This post-transcriptional mechanism has been reported for genes involved in drug metabolism, most notably cytochrome P450 (P450) (Turman et al, 2006), sulfotransferases (He et al, 2005), glutathione S-transferase (Ross and Board, 1993), and UDP-glucuronosyltransferases (UGTs) . UGT1A family members are derived from the use of alternative promoters and exons 1, whereas UGT2B7 is subjected to extensive alternative splicing (Innocenti et al, 2008;Guillemette et al, 2010;Ménard et al, 2011).…”
Section: Introductionmentioning
confidence: 99%